Feasibility of Enceladus plume biosignature analysis: Successful capture of organic ice particles in hypervelocity impacts. (4th September 2020) - New, James S.; Kazemi, Bahar; Price, Mark C.; Cole, Mike J.; Spathis, Vassi; Mathies, Richard A.; Butterworth, Anna L.
Abstract: Enceladus is a compelling destination for astrobiological analyses due to the presence of simple and complex organic constituents in cryovolcanic plumes that jet from its subsurface ocean. Enceladus plume capture during a flyby or orbiter mission is an appealing method for obtaining pristine ocean samples for scientific studies of this organic content because of the high science return, reduced planetary protection challenges, and lower risk and expense compared to a landed mission. However, this mission profile requires sufficient amounts of plume material for sensitive analysis. To explore the feasibility and optimization of the required capture systems, light gas gun experiments were carried out to study organic ice particle impacts on indium surfaces. An organic fluorescent tracer dye, Pacific Blue™, was dissolved in borate buffer and frozen into saline ice projectiles. During acceleration, the ice projectile breaks up in flight into micron‐sized particles that impact the target. Quantitative fluorescence microscopic analysis of the targets demonstrated that under certain impact conditions, 10–50% of the entrained organic molecules were captured in over 25% of the particle impacts. Optimal organic capture was observed for small particles ( d 5–15 µm) with velocities ranging from 1 to 2 km s −1 . Our results reveal how organic capture efficiency depends on impact velocity and particle size; capture increases as particles get smaller and as velocity is reduced. These results demonstrate the feasibility of collecting unmodified organic molecules from the Enceladus ice plume for sensitive analysis with modern in situ instrumentation such as microfluidic capillary electrophoresis (CE) analysis with ppb organic sensitivity.